Roles of exchange rate and interest rate risks in the stock valuation for selected East Asian economies - Virile (2008)
By looking at the significance of exchange rate and interest rate variables in determining industries stock return, this project attempts to examine whether or not selected East Asian economies are sensitive to exchange rate and interest rate fluctuations, and how these fluctuations affect the economies. The results obtained vary from nation to nation.